Secreted microvesicular miR‐31 inhibits osteogenic differentiation of mesenchymal stem cells. Issue 4 (4th May 2016) - Weilner, Sylvia; Schraml, Elisabeth; Wieser, Matthias; Messner, Paul; Schneider, Karl; Wassermann, Klemens; Micutkova, Lucia; Fortschegger, Klaus; Maier, Andrea B.; Westendorp, Rudi; Resch, Heinrich; Wolbank, Susanne; et al.
Summary: Damage to cells and tissues is one of the driving forces of aging and age‐related diseases. Various repair systems are in place to counteract this functional decline. In particular, the property of adult stem cells to self‐renew and differentiate is essential for tissue homeostasis and regeneration. However, their functionality declines with age (Rando, 2006). One organ that is notably affected by the reduced differentiation capacity of stem cells with age is the skeleton. Here, we found that circulating microvesicles impact on the osteogenic differentiation capacity of mesenchymal stem cells in a donor‐age‐dependent way. While searching for factors mediating the inhibitory effect of elderly derived microvesicles on osteogenesis, we identified miR‐31 as a crucial component. We demonstrated that miR‐31 is present at elevated levels in the plasma of elderly and of osteoporosis patients. As a potential source of its secretion, we identified senescent endothelial cells, which are known to increase during aging in vivo (Erusalimsky, 2009). Endothelial miR‐31 is secreted within senescent cell‐derived microvesicles and taken up by mesenchymal stem cells where it inhibits osteogenic differentiation by knocking down its target Frizzled‐3. Therefore, we suggest that microvesicular miR‐31 in the plasma of elderly might play a role in the pathogenesis of age‐related impaired bone formation and that miR‐31 might be a valuable plasma‐based biomarker for aging and for a systemic environment that does not favor cell‐based therapies whenever osteogenesis is a limiting factor.